Composts and organic by-products in Pinus halepensis forestry - Pérez-Piqueres, Ana; Moreno, Raquel; López-Martínez, Maria; Albiach, Remedios; Ribó, Marta; Canet, Rodolfo (Frontiers, 2018)
In the sustainable organic waste management context, this s tudy was carried out to explore the potential of easily available composts and orga nic by-products for Pinus halepensis forestry in Mediterranean areas. The study consisted in fou r experiments using locally abundant organic waste: experiments I and IV e valuated their suitability as fertilizers for nurseries and pine replanting respectiv ely; experiment II considered vermicompost efficiency as a root-growth promoter; experim ent III assessed the aptitude of organic waste as a component of forestry substrates. Diff erent plant measurements, morphological attributes and analytical determinations w ere used to assess seedling quality and to evaluate substrates and fertilizers’ aptitu de. Fertilization experiments run under nursery conditions showed that organic waste produce d plantlets with similar morphological and nutritional states to mineral products w ith good quality standards. In pine replanting, organic fertilization clearly increased soil organic matter levels, enhancing soil nutritional and structural conditions. When evaluatin g different mixtures as substrate, no large differences appeared among treatments, except for the seedlings grown in virgin or recycled coconut fiber, where greater aerial devel opment was achieved. Further research is needed to comprehend why the use of vermicompost as a root-growth promoter did not produce the expected effects. The obtained results indicate that organic by-products and composts can substitute the mineral fertil izers and substrates usually employed in the Mediterranean Region in P. halepensis forestry to contribute to develop a local circular economy.